Yoga e voz cantada : aplicação de técnicas do Yoga na pedagogia vocal = Yoga and the singing voice: application of Yoga techniques in vocal pedagogy - Souza, Laura Cirne de, 1958- (2019)
Orientador: Adriana Giarola Kayama